Validation of the Medical Professional Resilience Scale Among Malaysian Undergraduate Medical Students: A Confirmatory Factor Analysis - Mohd Bahar, Farhana Harzila; Roslan, Nurhanis Syazni; Abdul Nasir, Nurul Alimah; Ibrahim, Mohd Salami; Adam, Siti Khadijah; Ahmad Razali, Shazrina; Yusoff, Muhamad Saiful Bahri (Education in Medicine Journal, 2026)
Resilience is an essential attribute for medical professionals as they frequently encounter demanding academic, emotional, and clinical challenges. Reliable instruments are needed to assess resilience in medical education settings. The Medical Professional Resilience Scale (MeRS) was developed based on the integrated resilience model to measure resilience among healthcare professionals. However, validation of this instrument among undergraduate medical students remains limited. This study aimed to evaluate the construct validity and reliability of the MeRS among Malaysian undergraduate medical students using confirmatory factor analysis (CFA). A cross-sectional study was conducted among 242 undergraduate medical students from two Malaysian medical schools. The original MeRS consists of 37 items across four resilience domains such as growth, control, involvement, and resourcefulness. CFA was performed using IBM SPSS AMOS to evaluate the factor structure of the instrument. Model fit was assessed using absolute, incremental, and parsimonious fit indices. Model refinement was conducted by examining standardised factor loadings and modification indices. Composite reliability (CR), average variance extracted (AVE), and Cronbach’s alpha were calculated to assess reliability and convergent validity. The initial 37-item model demonstrated inadequate model fit. Sequential removal of poorly fit items resulted in a refined model consisting of 20 items. The final model demonstrated satisfactory goodness-of-fit indices (χ²/df = 1.438, CFI = 0.969, TLI = 0.965, GFI = 0.912, RMSEA = 0.043). Standardised factor loadings ranged from 0.58 to 0.98. CR values ranged from 0.79 to 0.88 and AVE values ranged from 0.46 to 0.69, indicating satisfactory reliability and convergent validity. The overall MeRS scale demonstrated good internal consistency with Cronbach’s α = 0.926. The findings support the construct validity and reliability of MeRS-20UG among Malaysian undergraduate medical students. The scale provides a concise, psychometrically sound instrument for assessing resilience in medical education settings.